2015
DOI: 10.15740/has/ajbs/10.2/167-170
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of wild plant extract for biological control of insect pests of Bt cotton

Abstract: Wild plant fruit extract such as hinganbet, Balanites roxburghii, ritthaa/soap nut, Sapindus trifoliatus, shikekaaee, Acacia concinna, Neem, Azadirachta indica, Karanj, Pongamia pinnata and vekhand, Acorus calamus L. were evaluated to screen their efficiency for the control of sucking pests of Bt cotton during Kharif 2009 to 2012 at Cotton Improvement Project, Mahatma Phule Krishi Vidyapeeth, Rahuri. All the organic pesticide treatments were superior over untreated control. Among the evaluated organic pesticid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…They have membrane-permeabilising, haemolytic, antioxidant, anti-inflammatory, immunostimulant and anticarcinogenic activities, and can affect feed intake, growth and reproduction in animals, and can be used as fungicides, molluscicides and pesticides, as well as against some bacteria and viruses. They can also increase mortality levels, lower food intake, weight reduction, retardation and disturbances in development, and decrease reproduction in insects [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have membrane-permeabilising, haemolytic, antioxidant, anti-inflammatory, immunostimulant and anticarcinogenic activities, and can affect feed intake, growth and reproduction in animals, and can be used as fungicides, molluscicides and pesticides, as well as against some bacteria and viruses. They can also increase mortality levels, lower food intake, weight reduction, retardation and disturbances in development, and decrease reproduction in insects [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thumar et al (2018) observed pyriproxyfen 10% EC @ 1000 ml/ ha as effective, whereas, Choudhary and Singh (2015) found three sprays of pyriproxyfen at 10 days interval as effective. Hole et al (2015) and Karkar et al (2014) obtained significant reduction with application of NSKE 5%. Pyriproxyfen 10%EC @ 1300/ 1000 ml; Diflubenzuron 25%WP @ 1314/ 300 gm; NSKE @ 250/ 25 kg; Labour and sprayer charges =2040 Rs/ ha; price of seed cotton Rs.…”
Section: Resultsmentioning
confidence: 93%
“…Thumar et al (2018) harvested maximum seed cotton yield with pyriproxyfen 10%EC, while Nemade et al (2017) obtained this with buprofezin 25SC. Kalyan et al (2017) also reported the cost effectiveness of buprofezin 25SC, while Hole et al (2015) harvested the satisfactory yield with NSKE 5%.…”
Section: Resultsmentioning
confidence: 96%
“…However, Choudhary et al (2015) reported that pyriproxyfen 10EC at different doses proved better than commercial check acetamiprid 20SP @ 20g a.i./ ha and difenthiuron 50WP @ 300g a.i./ ha in harvesting higher yields. Hole et al (2015) recorded seed cotton yield of 12.31 q/ ha in treatment with NSKE 5%.…”
Section: Resultsmentioning
confidence: 95%